Comparison of two strategies of reward-penalty mechanism for promoting net zero energy buildings - Lua, Yuehong; A.Khanb, Zafar; Gündüz, Hasan; Wang, Changlong; Imran, Muhammad; Qureshie, Imran (Elsevier Ltd, 2021)
Due to reduction of feed in tariff, the exploration of design solutions for smart cost-effective energy system is required to enable the consumers to select the optimum capacity of renewable energy system. This study investigates an innovative reward-penalty mechanism which is specifically designed to promote net zero energy buildings and net zero energy communities. Two different strategies (i.e. the building-level-based strategy and the community-level-based strategy) are developed regarding the application of the proposed reward-penalty mechanism. The electricity loads of family-houses in Ireland ranging from 1,286 kWh/y to 36,802 kWh/y are used to study the effect of the proposed strategies. The results show that both strategies lead to a similar cost versus zero-energy-building level relationship, i.e. a higher profit is related to a higher zero-energy-building level whilst a heavier financial penalty is related to a lower zero-energy-building level. The difference between the costs for the entire community (100 family-houses) predicted by the two different strategies is observed to be less than 10%. The building-level-based strategy is observed to produce the change rate of cost versus zero-energy-building level curve that often deviates significantly from the expected parabolic curve designed in this study, thus the community-level-based strategy provides an advantage over the building-level-based strategy. In addition, the Monte Carlo sampling method is used to quantify the uncertainty of the proposed reward-penalty function. © 2021 Elsevier Ltd
Keywords: Change rate of cost; Net zero energy building; Reward-penalty mechanism; Zero-energy-building level